Supporting teachers to actively respond to bullying and to build positive relationships with their students: effects of the T-SUPPORT training - Finet, Chloë; Vandebosch, Heidi; Lubon, Anouck; Colpin, Hilde (Frontiers in Psychology, 2023)
aims to reduce bullying and its negative consequences by supporting teachers in (1) promoting positive teacher-child relationships, and in (2) actively dealing with bullying. The study is innovative, first, by Besides testing teacher training as a specific intervention and not as part of a schoolwide program. Second, the training in this study adds to current teacher anti-bullying training by targeting teachers directly. and by including a focus on positive relationships. In existing anti-bullying intervention, teachers are often considered as 'intermediates' or 'facilitators' who transmit the program to the students, e.g., by giving lessons, rather than as the targets of the intervention (Gaffney et al., 2021). ; Research about teacher anti-bullying training as a stand-alone intervention targeting teachers directly is very scarce. A notable exception is the Bully Busters program (Newman-Carlson & Horne, 2004), a training aimed at strengthening teachers' effective intervention in bullying situations. A small-scaled quasi-experimental study found positive effects on teachers' self-reported knowledge about bullying, their responses to bullying, self-efficacy in dealing with bullying, and on (reduced) school referrals of bullying (Newman-Carlson & Horne, 2004), suggesting that teacher training targeting teachers' skills can be an effective strategy in tackling bullying. Research regarding the effects of teacher training on student perceptions is lacking, to the best of our knowledge. Last but not least, the T-SUPPORT training includes a focus on positive relationshipsFurther, whereas most existing teacher training, including Bully Busters, focuses on preventing and reducing negative student behavior and interactions, thereby missing the potential benefit of fostering positive teacher-student relationships. Referring to Gest and Rodkin (2011), promoting positive teacher-student relationships can be an additional approach to prevent bullying. Such an approach can be considered more feasible and desirable for teachers, because interacting with students is part of their job and, as such, the intervention can be integrated in their daily classroom routine.